A new species of Keratodegnathus Pace in Indonesia (Coleoptera, Staphylinidae) - Jałoszyński, Paweł (Zootaxa, 2024)
The genus Keratodegnathus Pace includes two species known to occur in Malaysia (Sabah and Pahang). A third species, Keratodegnathus javanicus sp. n. is described, based on a female specimen from Indonesia (West Java Province). As the morphology of Keratodegnathus was previously inadequately described, a detailed scanning electron microscopy examination was carried out to characterize the new species. Keratodegnathus mirabilis Pace, 2014 was transferred by Assing to Orphnebius Motschulsky, resulting in a secondary homonymy with Orphnebius mirabilis (Bernhauer, 1911). Orphnebius mirabilides nom. n. is proposed as a replacement name for Orphnebius mirabilis (Pace).